Activation of adenylate cyclase‐cyclic AMP‐protein kinase A signaling by corticotropin‐releasing factor within the dorsolateral bed nucleus of the stria terminalis is involved in pain‐induced aversion. (19th October 2016) - Kaneko, Tomoyuki; Kaneda, Katsuyuki; Ohno, Atsushi; Takahashi, Daiki; Hara, Taiki; Amano, Taiju; Ide, Soichiro; Yoshioka, Mitsuhiro; Minami, Masabumi
Abstract: Pain is a complex experience involving sensory and affective components. Although the neuronal mechanisms underlying the sensory component of pain have been extensively studied, those underlying its affective component have yet to be elucidated. Recently, we reported that corticotrophin‐releasing factor (CRF)‐induced depolarization in type II neurons within the dorsolateral bed nucleus of the stria terminalis (dlBNST) is critical for pain‐induced aversive responses in rats. However, the intracellular signaling underlying the excitatory effects of CRF and the contribution of such signaling to the induction of pain‐induced aversion remain unclear. In the present study, we addressed these issues by conducting whole‐cell patch‐clamp recordings in rat brain slices and by undertaking behavioral pharmacological analyses. Intracellular perfusion of protein kinase A (PKA) inhibitor Rp‐cyclic adenosine monophosphorothioate (Rp‐cAMPS) or KT5720 suppressed the excitatory effects of CRF in type II dlBNST neurons, and bath application of Rp‐cAMPS also suppressed it. In addition, bath application of forskolin, an adenylate cyclase (AC) activator, mimicked the effects of CRF, and pretreatment with forskolin diminished the excitatory effects of CRF. Furthermore, a conditioned place aversion (CPA) test showed that co‐administration of Rp‐cAMPS with CRF into the dlBNST suppressed CRF‐induced CPA. Intra‐dlBNST injection of Rp‐cAMPS also suppressed pain‐induced CPA. These results suggest that CRF increases excitability of type II dlBNST neurons through activation of the AC‐cAMP‐PKA pathway, thereby causing pain‐induced aversive responses. The present findings shed light on the neuronal mechanisms underlying the negative affective component of pain and may provide therapeutic targets for treating intractable pain accompanied by psychological factors. Abstract : Electrophysiological studies showed that CRF‐induced elevation of neuronal excitability in type II dlBNST neurons was suppressed by PKA inhibitors and mimicked by forskolin. In behavioral experiments, intra‐dlBNST injection of PKA inhibitors suppressed CRF‐ and pain‐induced aversive responses. These results suggest that CRF increases excitability of type II dlBNST neurons through activation of the adenylate cyclase‐cAMP‐PKA pathway, thereby causing pain‐induced aversive responses.